Taxonomy, Exploitation and Conservation of Dolphins in the Marine Waters of Ghana - Debrah, J.S. (University of Ghana, 2000)
Little is known about dolphins present in Ghanaian coastal waters. Taxonomic status, catch rate, and impact of the fishery on these animals, are areas, which have remained virtually untouched by previous workers. The present study attempts to fill-in these gaps in knowledge. Studies conducted during 1998 -2000 revealed the presence of the following eight species in Ghanaian waters: Stenella clymene, Stenella attenuata, Steno bredanensis, Tursiops truncatus, Grampus griseus, Lagenodelphis hosei, Globicephala macrorhynchus, and Delphinus capensis. S. Chlymene emerged as the most abundant species. Dolphin catches were low with peak period in August and September. Demand for dolphin meat for human consumption and bait for the shark fishery increased during the period of study. Though laws designed to protect and conserve dolphins exist on the Ghanaian statutes, little effort is made to enforce them. An educational programme, which would sensitize fisher folk on the issue of conservation, is also absent. Morphological taxonomy proved very useful in discriminating between species of dolphins encountered but no single character was found to be suitable. A combination of morphological characters, however, proved most effective. It was difficult to use biochemical characters possibly because the Delphinidae family, exists as polymorphic form of the same species.